Messiah in context Israel's history and destiny in formative Judaism - Neusner, Jacob, 1932- (Philadelphia, PA Fortress, 1984)
Includes bibliographical references and indexes.
Keywords: Messiah -- history of doctrines; Rabbinical literature -- history and criticism